Access to support during childbirth?: women's preferences and experiences of support person integration in a cross-sectional facility-based survey - Michelle K. Nakphong; Patience A. Afulani; James Opot; May Sudhinaraset (BMC, 2023)
Abstract Background Integrating support persons into maternity care, such as making them feel welcome or providing them with information, is positioned to increase support for women and improve birth outcomes. Little quantitative research has examined what support women need and how the healthcare system currently facilitates support for women. We introduce the Person-Centered Integration of Support Persons (PC-ISP) concept, based on a review of the literature and propose four PC-ISP domains-Welcoming environment, Decision-making support, Provision of information and education and Ability to ask questions and express concerns. We report on women's preferences and experiences of PC-ISP. Methods We developed PC-ISP measures based on the literature and applied these in a facility-based survey with 1,138 women after childbirth in six health facilities in Nairobi and Kiambu counties in Kenya from September 2019 to January 2020. Results We found an unmet need for integrating support persons during childbirth. Between 73.6 and 93.6% of women preferred integration of support persons during maternity care, but only 45.3-77.9% reported to have experienced integration. Women who reported having a male partner support person reported more PC-ISP experiences (B0.13; 95% CI 0.02, 0.23) than those without. Employed women were more likely to report having the opportunity to consult support persons on decisions (aOR1.26; 95% CI 1.07, 1.50) and report that providers asked if support persons should be informed about their condition and care (aOR1.29; 95% CI 1.07, 1.55). Women with more providers attending birth were more likely to report opportunities to consult support persons on decisions (aOR1.53; 95% CI 1.09, 2.15) and that support persons were welcome to ask questions (aOR1.84, 95% CI 1.07, 2.54). Conclusions Greater efforts to integrate support persons for specific roles, including decision-making support, bridging communication and advocacy, are needed to meet women's needs for support in maternity care.